Hubungan antara organisasi pergerakan mahasiswa islam indonesia (pmii) dengan nilai-nilai islam ahlus sunnah wal jama’ah - Fuad, Fuad Ali Maskur (Maliki Interdisciplinary Journal, 2025)
PMII, as an organization rooted in Islam, aims to shape young generations who not only possess a broad understanding of religion but also uphold Islamic values that are moderate, inclusive, and rational in accordance with the teachings of Ahlus Sunnah Wal Jama’ah. PMII has a close relationship with the Islamic values of Ahlus Sunnah Wal Jama’ah in nurturing its members. This organization emphasizes moderate Islamic principles in all its activities, whether in scholarly discussions, personal development, or character building for students. Values such as tawassut (moderation), tasamuh (tolerance), and ijtihad (critical reasoning) are taught within the framework of Ahlus Sunnah Wal Jama’ah, encouraging students to think openly and inclusively without abandoning strong religious foundations. Therefore, PMII not only plays a role in strengthening the religious understanding of its members but also serves as a platform for instilling moderate Islamic values in line with the teachings of Ahlus Sunnah Wal Jama’ah.